Double jeopardy : globalization, liberalization and the fiscal squeeze - Grunberg, Isabelle (1998)
Attempts to substantiate a 'fiscal squeeze' model of the effect of globalization. Outlines avenues for further, more systematic assessment of the phenomenon. Illustrates the 'squeeze' hypothesis with reference to two simultaneous phenomena - pressure on the spending side, and pressure on the revenue side. Analyzes distributional implications by using the example of the currency crises in South East Asia.